The Relationship Between Variations in Teaching Skills of Tutors and Learning Motivation of Learning Package C Students in SPNF SKB Kota Pariaman - Dilia, Reschia Nofour; Irmawita, Irmawita (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
ABSTRACTThe aim of this research is to find out the description and relationship between skills in applying variations in tutor teaching and the learning motivation of residents studying Package C at SPNF SKB Kota Pariaman. This research uses quantitative correlational. The population of this research is all students registered in the package C pursuit program at SPNF SKB Kota Pariaman for the 2023/2024 academic year, namely 72 people. The sampling technique used cluster random sampling, so that the total sample that the researchers took was 50 residents studying package C at SPNF Kota Pariaman. Data collection techniques using questionnaire format and list of statements as data collection tools, data analysis techniques using percentages to find correlations using the product moment formula. The results of this research are: 1.) Skills in applying variations in tutor teaching to students studying at SPNF SKB Kota Pariaman are classified as less than optimal, 2.) Motivation of students studying Package C at SPNF SKB Kota Pariaman is classified as less than optimal and 3.) There is a significant relationship between skills in applying variations in tutor teaching with learning motivation for residents studying Package C at SPNF SKB Kota Pariaman.Keywords: Variasi Mengajar, Motivasi Belajar, SKB.